The imperative of retaining contact with the remote distance learner: A perspective from Uganda - Chris Acer; Tony Wrightson (Flexible Learning Association of New Zealand, 2012)
Developing countries confront major challenges in providing educational opportunities, particularly those ravaged by civil war, or poor in resources, or experiencing rapid population growth. In Uganda efforts are being made to revivify primary education in the northern regions of the country by training working primary teachers. The distance delivery system employed is described and the paper concludes that formal student support systems are by themselves insufficient to ensure success in learning at a distance.